Association between functional disability and depressive symptoms among older adults in rural China: a cross-sectional study - Hong Ding; Jian Rong; Xueqin Wang; Yanhong Ge; Guimei Chen (BMJ Open)
Objectives The aim of this study was to explore the relationship between functional disability and depressive symptoms, focusing on whether an interaction exists between functional disability, demographic characteristics and depressive symptoms among older adults in rural China.Design A cross-sectional study using multistage, stratified random sampling.Setting Data from 18 villages in Anhui Province of China between January to July 2018.Participants 3491 Chinese participants aged 60 and over.Primary and secondary outcome measures The 30-item Geriatric Depression Scale and WHO Disability Assessment Schedule 2.0 were used to evaluate depressive symptoms and functional disability, respectively. Data were analysed using SPSS statistics V.25.0 program with χ2 test, Mann-Whitney U test, binary logistic regression analysis and classification and regression tree (CART) model.Results The prevalence of depressive symptoms in 3336 interviewed older people was 52.94%. After adjustment, subjects who had problems in mobility domain (adjusted OR (AOR) 1.842, 95% CI 1.503 to 2.258), getting along domain (AOR 1.616, 95% CI 1.299 to 2.010), life activities domain (AOR 1.683, 95% CI 1.370 to 2.066) and participation domain (AOR 3.499, 95% CI 2.385 to 4.987) had an increased depressive symptoms risk. However, cognition domain (AOR 0.785, 95% CI 0.647 to 0.953) negatively correlated with depressive symptoms. Additionally, the CART model showed that those who had problems in mobility domain, getting along domain and were unemployed, the possibility of having depressive symptoms was the highest.Conclusions More attention should be paid to unemployed older adults, and those with problems in participation, life activities, getting along and mobility and no problems in cognition to maintain a good psychological state.